Pengaruh Green Accounting Terhadap Nilai Perusahaan Sektor Energi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2018 - 2022 - Yani, Verah; Wijaya, Trisnadi (Universitas Multi Data Palembang, 2024)
The aim of this research is to test and analyze the relationship between green accounting and company value. This research uses secondary data, namely financial reports and annual reports. This research surveyed 17 Energy Sector Companies listed on the IDX between 2018-2022. The sampling technique used was purposive sampling. Research data was analyzed using multiple linear regression analysis. The research results show that green accounting has a significant effect on company value.